Measurement and Meaning : Combining Quantitative and Qualitative Methods for the Analysis of Poverty and Social Exclusion in Latin America - Gacitua-Mario, Estanislao; Wodon, Quentin (Washington, DC: World Bank, 2013)
This report consists of a collection of case studies from Latin America combining qualitative and quantitative research methods for the analysis of poverty within a social exclusion framework. The first chapter provides an overview of the differences between quantitative and qualitative methods, and the gains from using both types of methods in applied work. The other chapters are devoted to three case studies on reproductive health in rural Argentina, the targeting of social programs in Chile, and social exclusion in urban Uruguay. Each case study was prepared within the broader context of country-specific economic and sectoral work at the World Bank.